The Norwegian research program on the Barents Sea capelin stock - Dommasnes, Are (ICES, 1977)
The aim of the Norwegian research program on the Barents Sea capelin stock is to provide information needed for management of the fishery. The cruise program for 1977 and the objectives of each cruise is discussed. The sampling program and processing of information is also described.